Experimental and Theoretical Investigation of the Acoustic Absorbers Fabricated from Natural Kenaf Fibres and Rice Husk. Issue 16 (28th November 2022) - Etemadinezhad, Siavash; Samaei, Seyed Ehsan; Taban, Ebrahim; Faridan, Mohammad
ABSTRACT: Fabrication of acoustic absorbers from a combination of natural waste materials is a novel approach in the field of noise control. The aim of this study was to investigate the acoustic absorption performance of several sample sound absorbers made from natural kenaf fibers and rice husk. A new method of fabricating these sample sound absorbers was also employed to study the usability as well as performance improvement via the approach fibro-granular sound absorbers (FGSA). The values of acoustic absorption performance, porosity, and airflow resistivity of the samples were used in the experimental design. The Dunn and Davern (D-D) theoretical model as well as the reversed D-D model with Nelder–Mead Simplex were applied to evaluate the sound absorption as well. According to the obtained values, it was found that at low- and mid-frequency range, the sound absorption value of FGSA is higher than other acoustic materials. The FGSA (with a density of 150 kg/m 3 ) increased noise reduction coefficient value by 31.25% compared to samples fabricated to the rice husk and also by 10.53% compared to kenaf. Based on comparison of the theoretical and experimental results, the model optimized with the Nelder–Mead method had higher accuracy and fitting in predicting the sound absorption values than the D-D model. Finally, it was found that improvement in the sound absorption performance of the natural acoustic absorbers might be achieved through adopting the approach of combining natural materials and fabrication of FGSA.